Building Public Trust in Indonesia’s Legal System: Case Analysis and Social Implications - Syahrir, Mukum; Anindito, Firman Dwi; Nugroho, Dwi Cahyo (LPPM Universitas Sains dan Teknologi Komputer, 2025)
Public trust in the legal system plays a pivotal role in ensuring the legitimacy and effectiveness of law enforcement in democratic societies. In Indonesia, recurring issues such as judicial inconsistency, law enforcement bias, and unequal access to legal services have contributed to a crisis of confidence among citizens. This study aims to investigate the determinants of public trust in Indonesia’s legal system and to explore the broader social implications through a qualitative case study approach. Data were collected using in-depth interviews with key informants—including legal academics, activists, and citizens—complemented by media content, court rulings, and NGO reports. Thematic analysis, facilitated by ATLAS.ti, revealed three primary dimensions of legal trust: procedural justice, distributive justice, and restorative justice. Key findings show that personal experiences with legal institutions, media portrayal of legal cases, and the quality of institutional communication significantly influence public perceptions of the legal system. Participants who experienced discrimination or unequal treatment expressed higher levels of distrust, while others acknowledged the credibility of institutions such as the Constitutional Court. This study also finds that a lack of proactive and empathetic institutional communication undermines transparency and public legitimacy. The research contributes theoretically by integrating sociological and legal perspectives to understand how legal legitimacy is socially constructed. Practically, the findings highlight the need for structural and communicative reforms to rebuild public confidence in legal institutions. Ultimately, this study argues that trust in the legal system cannot be restored solely through legal formalism, but must also involve participatory engagement and equitable access to justice, especially in the context of Indonesia's evolving socio-political landscape.